Evaluation of the Application of Blended Learning in Arabic Learning at Sidoarjo Junior High School - Lailatul Farikhah; Farikh Marzuki Ammar (Indonesian Journal of Islamic Studies, 2023)
Blended learning is a mixture of traditional education as well as an area of ​​electronic education. Blended Learning is defined as Blended from the initial word "Blend" which is a blend or mixing, while learning comes from the word "learn" which means learning, studying, listening. From this explanation, the researcher appointed a research entitled Evaluation of the Application of Blended Learning in Arabic Learning at SMP Muhammadiyah 1 Sidoarjo. The study used qualitative methods with interviews conducted to determine the evaluation of the application of blended learning which was carried out face-to-face.